The levels of the blood serum thyroid hormones, glucose and total cholesterol in breeds of pointers, german shepherd and kangal dogs - Tufan Keçeci; Zafer Durgun (Eurasian Journal of Veterinary Sciences)
In this study, the levels ol serum thyroid hormones, glucose and total cholesterol were determined tn a total of 36 dogs which were clinically healthy and at the same conditions of maintenance and nutrition. For this purpose, mate and female Pointers, German Shepherd Dogs (GSD) and Kangal Dogs which were equal numbers for per breeds were used, and investigated parameters were compared acording to differences of sex and breeds. The required blood was drawn from vena jugularis and the serum was obtained. There were no significant differences in all of the investigated parameters between male and female in the dogs. The serum total triiodothyronine level was lower amounts in the GSD (mean 28.5 kg body weight) and Kangal dogs (mean 30.2 kg body weight) which were admitted the large breeds, when compared to the Pointers (mean 19 8 kg body weigh!) which is admitted the medium breed. Although, it was not determined significant differences at the levels of total thyroxine, glucose and total cholesterol among the three breeds ol dogs On the other hand, it was generally found that significant positive correlation between serum thyroid hormones and glucose levels, and negative correlation between thyroid hormones and total cholesterol levels.